Advances in the Regulation of Periostin for Osteoarthritic Cartilage Repair Applications - Sunny Y. Shih; Michael P. Grant; Laura M. Epure; Muskan Alad; Sophie Lerouge; Olga L. Huk; Stephane G. Bergeron; David J. Zukor; Géraldine Merle; Hee-Jeong Im; John Antoniou; Fackson Mwale (Biomolecules)
Emerging evidence indicates periostin (POSTN) is upregulated in patients with OA, and studies have shown that it can induce the activation of inflammatory cytokines and catabolic enzymes, making it a potential therapeutic target. Link N (LN) is a peptide fragment derived from the link protein and has been demonstrated as an anabolic-like factor and anti-catabolic and anti-inflammatory factors both in vitro and in vivo. This study aims to determine if LN can regulate POSTN expression and function in OA cartilage. Articular cartilage was recovered from donors undergoing total knee replacements to isolate chondrocytes and prepare osteochondral explants. Cells and explants were treated with POSTN and LN (1 and 100 μg) and measured for changes in POSTN expression and various matrix proteins, catabolic and proinflammatory factors, and signaling. To determine the effects of POSTN expression in vivo, a rabbit OA model was used. Immunoprecipitation and in silico modeling were used to determine peptide/POSTN interactions. Western blotting, PCR, and immunohistochemistry demonstrated that LN decreased POSTN expression both in vitro and in vivo. LN was also able to directly inhibit POSTN signaling in OA chondrocytes. In silico docking suggested the direct interaction of LN with POSTN at residues responsible for its oligomerization. Immunoprecipitation experiments confirmed the direct interaction of LN with POSTN and the destabilization of its oligomerization. This study demonstrates the ability of a peptide, LN, to suppress the overexpression and function of POSTN in OA cartilage.